Choline Kinase Alpha Is a Novel Transcriptional Target of the Brg1 in Hepatocyte: Implication in Liver Regeneration - Kong, Ming; Dong, Wenhui; Xu, Huihui; Fan, Zhiwen; Miao, Xiulian; Guo, Yan; Li, Chengping; Ye, Qing; Wang, Yutong; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Liver regeneration is a key compensatory process in response to liver injury serving to contain damages and to recover liver functions. Hepatocytes, having temporarily exited the cell cycle after embryogenesis, resume proliferation to regenerate the injured liver parenchyma. In the present study we investigated the transcriptional regulation of choline kinase alpha (Chka) in hepatocytes in the context of liver regeneration. We report that Chka expression was significantly up-regulated in the regenerating livers in the partial hepatectomy model and the acetaminophen injection model. In addition, treatment with hepatocyte growth factor (HGF), a strong pro-proliferative cue, stimulated Chka expression in primary hepatocytes. Chka depletion attenuated HGF-induced proliferation of hepatocytes as evidenced by qPCR and Western blotting measurements of pro-proliferative genes as well as EdU incorporation into replicating DNA. Of interest, deletion of Brahma-related gene 1 (Brg1), a chromatin remodeling protein, in mice attenuated Chka induction in the regenerating livers and in cultured hepatocytes. Further analysis revealed that Brg1 interacted with hypoxia-inducible factor 1 alpha (HIF-1a) to directly bind to the Chka promoter and activate Chka transcription. Finally, examination of human acute liver failure (ALF) specimens identified a positive correlation between Chka expression and hepatocyte proliferation. In conclusion, our data suggest that Brg1-dependent trans-activation of Chka expression may contribute to liver regeneration.